The Impact of Social Media Marketing on College Selection Mediated By Brand Image: Case Study on @officialunila Instagram Account - Sentosa, Budi; Bangsawan, Satria; Wulan, Mutiasari Nur (Papanda Publisher, 2025)
Increasing competition among universities has prompted Lampung University to optimize its digital marketing strategies through social media, yet the @officialunila Instagram account faces challenges in effectively attracting prospective students despite significant engagement growth. This study examines the relationship between social media marketing and students' college selection decisions, with brand image serving as a mediating variable, using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze data from 390 Lampung University students from the class of 2024. The findings reveal that social media marketing has a strong positive correlation with brand image (path coefficient = 0.708; p-value = 0.000) and college selection decisions (path coefficient = 0.167; p-value = 0.000), while brand image significantly influences selection decisions (path coefficient = 0.752; p-value = 0.000) and effectively mediates the relationship between social media marketing and selection decisions through complementary mediation (path coefficient = 0.532; p-value = 0.000). The results demonstrate that social media marketing significantly impacts prospective students' decision-making processes both directly and indirectly through brand image enhancement, suggesting that Lampung University should continue managing the @officialunila Instagram account professionally by creating informative and engaging content tailored to digital generation preferences to strengthen brand image and attract prospective students.